The Effectiveness of Relaxation Therapy on Symptoms and Quality of Life in Hemodialysis Patients: A Literature Review - Rabiatul Addawiah; Yulia Yulia; Sri Yona (Indonesian Journal of Global Health Research, 2024)
Hemodialysis (HD) is the main therapy for patients with end-stage renal disease (ESRD) in Indonesia, but the patients' quality of life is lower than other methods due to the physical and psychological effects of HD. One of the therapies that can be used to reduce the effects of HD is relaxation therapy. Objective: This review aims to analyse the effectiveness of relaxation therapy in managing physical and psychological symptoms to improve the quality of life of HD patients. Method: A literature review using databases such as Pubmed, Science Direct, Scopus, Sage Journal and Proquest to search for relevant articles within the period 2020-2024. Results: A review of twelve articles shows that relaxation therapy is effective for pain, fatigue, stress, depression, anxiety, sleep quality and patient quality of life. Conclusions: Relaxation therapy can be integrated into routine care and is feasible for nurses to provide because of its simplicity so that patients can do it themselves at home. Nurses also need to conduct further research into other non-pharmacological therapies that are widely effective for patients with ESRD.